Geotechnical Properties for Soil Alghlabia Area in Diyala Governorate /North Baghdad/ Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The research aims, to find out the geotechnical properties for soil Alghlabia area, locate within the near (HibHib) in Khalis/Diyala, northeast of Iraq. Just (17) km from the district center, (46) km from the center of Baghdad, five samples were taken from five sites in the area. Physical properties show that the types of soils, (CL-ML, CL) according to the  classification. Activity of soil values normal, Liquid limit (L.L.) and plasticity index(P.I)and depending on plasticity chart the soils type respectively (ML, ML, CL-ML, ML, CL-ML), while the specific gravity (Gs) values converge, because  resources of same sediments,  porosity (n%) & voids ratio (e0) values for three site are different , dry density (ρd) values approximate for values set by Mechanical properties, direct shear test show that the values cohesion C & angle of internal frication (Ø) are with the natural range of known values of clay soils, while the consolidation test for sites shows that the normal values, Pre consolidation pressure (pc), compression index (cc) & swelling index (cr), then the values of Over Consolidation ratio (OCR) greater than 1, which indicate over consolidation soils. Chemical analysis .Total dissolve salts (T.D.S) for sites is higher exceeded 0.5%, Gypsum content less than 0.5%.Organic Matter content (O.M.C) less than (0.5%)& (pH) the result show that the soil is basic. According to standard, it was suitable, for different Engineering construction.